Upper Limb Meromelia with Oligodactyly and Brachymesophalangy of the Foot: An Unusual Association - Meltem Özdemir; Rasime Pelin Kavak; Önder Eraslan (Case Reports in Radiology)
Meromelia is a rare skeletal abnormality characterized by the partial absence of at least one limb. Several mechanisms have been postulated to explain the etiopathogenesis of the disorder. Most of the cases of meromelia are reported to be sporadic. It can occur either in isolation or with other congenital malformations. VACTERL association, gastroschisis, atrial septal defect, proximal femoral focal deficiency, and fibular hemimelia are the congenital abnormalities reported to be in association with meromelia. However, no other congenital abnormalities in association with meromelia have been recorded to date. We herein present an unusual case of bilateral upper limb meromelia accompanied by unilateral oligodactyly and brachymesophalangy of the foot.